Altas habilidades ou superdotação: formação de professores para os anos iniciais do ensino fundamental - Rosa, Elaine de Menezes Rocha (Universidade Federal de São Carlos, 2025)
This research addresses the topic of Giftedness: Teacher training for the early years of elementary school. The research has a descriptive approach with a case study. The general objective was to investigate the context of teacher training on the topic of giftedness in the early years of elementary school in public and private schools linked to the Municipal Education Board of the City of São Paulo, and the specific objectives were: i) Checking whether there is a difference in knowledge among teachers at two schools, one public and one private; ii) finding out how the teachers surveyed received training/education on the subject; and iii) verify the possible experiences of teachers who have worked or are working with gifted students. The research was conducted in two elementary schools (one public and one private) linked to the Municipal Education Board of the City of São Paulo in the western part of the capital. Twenty-seven teachers participated in the study. Two data collection instruments were created: a semi-structured questionnaire to the teachers to assess their knowledge of the topic, and a form about myths in the school and the social and economic contexts. The results showed that: a) the teaching staff at the schools surveyed reported that 52% had knowledge of the topic of giftedness; b) when observing the scenarios, separately, the data showed that public school teachers had less contact with the topic, 20% of teachers had knowledge and 80% without it. However, in private schools, the opposite was observed with 71% stating that they had information about giftedness and 29% unknew of it; c) There were teachers' perceptions about myths of gifted students in both schools; d) 53% of teachers received information on the subject through undergraduate studies, 27% through specialization courses, 7% through in-service training, and 13% through the media; e) 74% of teachers of the schools had not worked with gifted students and 100% of public school teachers reporting a lack of recognition of those students. Therefore, it is suggested that these educators receive training on giftedness so that, in the future, they can support the students.
Giftedness: teachers' formation for the early years at elementary school
Keywords: Educação Especial; Formação de professores; Altas Habilidades ou Superdotação; Ensino Fundamental; Special Education; Teacher training; Giftedness; Elementary School; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade